The Elaboration and Implementation of a Digital Educational Game Using a Low Cost Interactive Digital Whiteboard - Figueroa, Claudia Araceli; Solís Cortés, Fernando Félix; Corral Hurtado, Susana (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2014)
The teachers’ interest for creating an innovative and interactive learning approach has fostered the curiosity for creating Learning Objects in the form of interactive games that can be adapted to any topic and educational level by using digital resources such as Interactive Whitebords (IWBs).Taking into consideration that using the traditional IWBs involves a high economic investment, same that leads to a limited availability for teachers, a low-cost alternative has been found that can replicate the same features of interactivity that can be found in the leader commercial brands of IWBs. Such implementa-tion was carried out in conjunction with the development of a Learning Object (LO) in the form of a digital interactive game, which was the result of a final draft of the 'design of learning objects' class belonging to the Faculty of Education and Educa-tional Innovation of Universidad Autónoma de Baja California, in Mexicali, Baja California, Mexico.